2015
DOI: 10.1088/0031-9155/60/8/3151
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave elastography plaque characterization with mechanical testing validation: a phantom study

Abstract: Determining plaque vulnerability is critical when selecting the most suitable treatment for patients with atherosclerotic plaque. Currently, clinical non-invasive ultrasound-based methods for plaque characterization are limited to visual assessment of plaque morphology and new quantitative methods are needed. In this study, shear wave elastography (SWE) was used to characterize hard and soft plaque mimicking inclusions in six common carotid artery phantoms by using phase velocity analysis in static and dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 48 publications
1
55
0
Order By: Relevance
“…Ramnarine et al (2014) recently conducted a study involving eighty-one patients and demonstrated that shear wave elastography (SWE) is able to quantify carotid plaque elasticity and provide clinically relevant information to help identify unstable carotid plaques (Ramnarine et al 2014). Widman et al (2015) compared shear moduli of hard and soft plaques in vessel phantoms measured using SWE to mechanical testing results, and validated the feasibility of characterizing in vivo carotid plaque using SWE (Widman et al 2015). Korukonda et al (2013) studied sparse-array elastography and compared it to plane-wave imaging and compounded-plane-wave imaging on simulated vessel and vessel phantoms (Korukonda et al 2013).…”
Section: Introductionmentioning
confidence: 83%
“…Ramnarine et al (2014) recently conducted a study involving eighty-one patients and demonstrated that shear wave elastography (SWE) is able to quantify carotid plaque elasticity and provide clinically relevant information to help identify unstable carotid plaques (Ramnarine et al 2014). Widman et al (2015) compared shear moduli of hard and soft plaques in vessel phantoms measured using SWE to mechanical testing results, and validated the feasibility of characterizing in vivo carotid plaque using SWE (Widman et al 2015). Korukonda et al (2013) studied sparse-array elastography and compared it to plane-wave imaging and compounded-plane-wave imaging on simulated vessel and vessel phantoms (Korukonda et al 2013).…”
Section: Introductionmentioning
confidence: 83%
“…These studies show that the technique is clinically safe and provides reproducible shear wave velocity estimates, also in vivo [3,4,7]. Experimental studies with vessel-mimicking phantoms also showed that local regions with softer tissue can be detected [4,8,9], hence they show that the technique might be used to detect soft lipidrich/necrotic cores. However, all these studies image arteries in a longitudinal imaging view, which is useful only for imaging the centre plane of the vessel and not for detecting lipids over the full vessel circumference.…”
Section: Introductionmentioning
confidence: 63%
“…Especially this last assumption is not valid for thin-walled vessels. Because of the limited thickness of the tissue, dispersion, refraction and reflection will occur as also demonstrated for vascular shear wave elastography in longitudinal imaging planes [2,7,9]. In those phantom studies shear wave phase velocity instead of group velocity was found to allow a more correct quantification of tissue stiffness.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, with phantom studies [15] successfully resolving plaque stiffness over a range corresponding to what is reported for atherosclerotic plaque tissue [14], the performed study should serve as a proof-ofconcept example, with the ability to perform similar testing of a plaque investigated directly following surgical extraction.…”
Section: Discussionmentioning
confidence: 99%